1970
DOI: 10.1111/j.1752-7325.1970.tb00532.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Two Educational Programs in Changing the Performance of Oral Hygiene by Elementary School Children

Abstract: Doctor Podshadley andMiss Schweikle have to conclude: "Sorry folks, but your single annual lecture and demonstration of toothbrushing for children in the third and fourth grades is not effective in changing their performance, regardless of their choice of two technics. "Good oral hygiene for a long period has been considered an important factor in the prevention of periodontal disease and the activity of dental caries. Although various methods have been utilized t o obtain good oral hygiene, the most widely ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…Becker et al (1977) found that assessment acted as a "motive arousing intervention" which produced a marked improvement in compliance to a dietary regimen. Similar effects of assessment have also been found for improved dental hygiene (Evans et al, 1970;Podshadley and Schweikle, 1970;Ramer, 1979) and cessation of cigarette smoking (Best et al 1977).…”
Section: Introductionsupporting
confidence: 51%
“…Becker et al (1977) found that assessment acted as a "motive arousing intervention" which produced a marked improvement in compliance to a dietary regimen. Similar effects of assessment have also been found for improved dental hygiene (Evans et al, 1970;Podshadley and Schweikle, 1970;Ramer, 1979) and cessation of cigarette smoking (Best et al 1977).…”
Section: Introductionsupporting
confidence: 51%
“…Williford et al reported that educational lectures result in highly significant improvements in oral health when applied in adolescents [13]. Doctor Podshadley and Miss Schweikle from the results of their study quoted, "Sorry folks, but your single annual lecture and demonstration of tooth brushing for children in the third and fourth grades are not effective in changing their performance, regardless of their choice of two techniques" [14]. Thus there lies a need of newer comprehensive methods for teaching brushing technique in children, wherein attention may be given to individual needs of each child.…”
Section: Discussionmentioning
confidence: 99%
“…However within 6 months after the intervention, the improvements in oral hygiene were no longer present (Anerud 1969& Gjermo 1967. Similarly, research findings in other areas of health care indicate that providing educational information alone will not alter behavior (Albino et al 1977, DiMattio & DiNicola 1984, and Podshadley & Schweikle 1970.…”
mentioning
confidence: 99%